Anticancer Structure‐activity Relationships and Potential Target Exploration of the Natural Product Gypsogenin. Issue 10 (7th March 2023) - Sun, Kang‐Ping; Zhao, Ting‐Ting; Liu, Lei; Mu, Xiao‐Dong; Sun, Jing‐Yong
Abstract: Combined with molecular docking and molecular dynamic (MD) simulation, the derivative directions and structure‐activity relationships of the compounds were initially explored. Nineteen gypsogenin derivatives were synthesized and screened for cytotoxic activities. Their structures were established using IR, 1 H NMR, 13 C NMR, and LC–MS spectroscopic data. In the CCK‐8 assays, most of the compounds displayed good cytotoxicity in the low μΜ range for several human tumor cell lines (A549, MCF‐7 and LOVO). The bioassay test suggested that most of these derivatives showed antitumor activities. In particular, some compounds posed moderate antitumor activity. They may be related to start the process of apoptosis and lead to cell death. Abstract : We reported the molecular docking study and molecular dynamic simulation of gypsogenin and derivatives with some proteins related to cancer treatment, and a series of new gypsogenin derivatives were designed and synthesized.